Integrasi Kadar Proksimat dan Mutu Sensoris Pakan Ikan Organik Berbasis Tepung Ampas Kelapa Terfermentasi dan Tepung Jangkrik - Aprilia, Nadia; Asngad, Aminah (Universitas Muhammadiyah Prof. Dr. Hamka, 2024)
Background: Feed is a determining factor in the success of fish farming, but in some cases, fish feed on the market contains chemicals such as pesticides, heavy metals, and synthetic chemicals. Organic, safer, and readily available materials combine plant-based and animal ingredients such as cricket (Acheta domesticus) and coconut pulp. Cricket has a high nutritive value, especially protein content, and coconut pulp was potentially high in carbohydrate content. The study aims to determine the carbohydrate and protein content and the color, aroma, and density assessment of the combination of fermented coconut pulp flour and cricket flour. Methods: The design pattern was a 1-factor Completely Randomized Design (CRD) pattern with two repetitions of 3 treatments (A1, A2, and A3) of fermented coconut pulp flour and cricket flour. Feed is subjected to tests on carbohydrate and protein proximate levels and sensory assessments of its color, aroma, and texture. Results: The average carbohydrate content in formulas A1, A2, and A3 is 30.51%, 26.04%, and 28.45%, while the protein content is 10.64%, 20.88%, and 16.86%. ANOVA test results on color, aroma, and overall texture show significant differences in each fish feed formula. Conclusions: The highest level of sensory preference for color, aroma, and texture was observed in the combination of formula A2. Formula A1 is suitable for herbivorous fish, formula A2 for carnivorous fish, and formula A3 for omnivorous fish.